Factors Affecting Investment Behavior of Working Women - Suwal, Indu (Shahid Kirti Multidisciplinary Journal, 2025)
Working women are being financially independent and want to invest their saving for family welfare and for long- term purpose. Working women and their investment behavior is crucial as their income affect Gross Domestic Product of the country. Working women can also make personal financial planning to achieve financial goal with their own decision. It can be observed that involvement of women in investment sector with great enthusiasm as the economic scenario is changing. This study has been done with the objective of exploring the investment decision from the perspective of working women in Kirtipur. This study identifies various factors that affect the investment decision of women investors. The information was gathered through structured questionnaire distributed to the 391 working women of Kirtipur. The data has been analyzed using SPSS software by applying descriptive statistics. The study showed that the investment decision of working women is greatly influenced by social factor and information factor. Similarly, firm's image also shows the strong correlation with investment decision but psychological factor doesn't affect significantly to the investment decision. This study can be supportive for educational programs and policy formulation which can enable women investors in making financial decision..